A Theoretical Framework for Evaluating the Impact of Universal Reserve Requirements - Sprenkle, Case M.; Stanhouse, Bryan E. (Journal of Finance, 1981)
This paper provides an appropriate framework to evaluate the impact of the universal reserve requirements called for by the new DIDMC Act of 1980. We derived the optimal reserve ratios for a dual banking system under the objective of controlling the monetary aggregates and the level of output. Then optimal reserve requirements were calculated from illustrative money market and macroeconomic parameters since the usual comparative statics were not useful. The results, generally, suggested optimal reserve ratios which were significantly higher than the old dual or the new universal reserve regimes for all targets. However, the calculation of values for the loss functions under various reserve regimes suggests that attainment of r 1 * , r 2 * and t * may not be imperative, since the discrepancy between losses for optimal and various nonoptimal reserve schemes were not large. A major result of this paper, observed for both monetary and real targets, was that the differences in the instability of the targets for the old dual reserve ratios and the Fed's new universal reserve scheme were small. This result clearly suggests that although the DIDMC Act may solve the Federal Reserve's membership problem, it will not significantly enhance the Fed's effectiveness in controlling monetary or real sector aggregates.